THE INFLUENCE OF IMPLEMENTING THE STAD TYPE COOPERATIVE LEARNING MODEL (STUDENT TEAM ACHIEVEMENT DIVISIONS) ON MATHEMATICS LEARNING OUTCOMES AT MUHAMMADIYAH 1 PRIMARY SCHOOL BANDA ACEH - Fitriyasni Fitriyasni; Nazariah Nazariah (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2023)
One of the reasons students do not understand mathematical concepts is because mathematics is often introduced as a collection of abstract numbers and formulas. For this reason, it is necessary to use teaching aids that are appropriate to the material being studied, in order to minimize the characteristics of abstract mathematical material. Another reason students experience difficulties in learning mathematics is that the mathematics learning process is still in one direction and the dominance of teacher activity in learning activities so that students are less active in participating in the mathematics learning process. As a result, the expected learning outcomes will be less than optimal and learning activities are felt to be less meaningful and useful for students. Therefore, it takes a learning that can make students active and creative in constructing a problem solving through certain media. From this, research was carried out on learning at SD Muhammadiyah 1 Banda Aceh. This learning was carried out in five stages, namely: (1) Class presentation stage, (2) Group discussion stage and report presentation, (3) Individual test stage, (4) Point determination stage for individual and group development, (5) Award giving stage. This aims to describe student learning outcomes, student activities, teacher activities and student responses to learning activities using domino cards with the STAD type cooperative model. In this study, the population was all students at SD Muhammadiyah 1 consisting of 220 students. Since this is an experimental study, the sample is divided into experimental and control groups. The researcher took class IV A as the experimental class which consisted of 19 students and class IV B which consisted of 20 students as the control group. In summary, based on the research results, the researcher concluded that the STAD type cooperative learning model proved to be a suitable technique that could be used to teach mathematics to students, because it had also been proven through quantitative data analysis. Keywords:  Application; cooperative; STAD models; Learning outcomes